Role of interventional radiology in the management of postoperative gastrointestinal leakage - Ji Hoon Kim; Ji Hoon Shin; Jung Suk Oh (Society of Gastrointestinal Intervention, 2022)
Gastrointestinal (GI) leakages after surgery are significant complications that are associated with high morbidity and mortality. Due to recent technology advancements, interventional management of postoperative GI leakage may be a better alternative than surgical treatments in terms of less invasiveness, decreased mortality, morbidity, and hospital stay. Furthermore, new interventional management techniques are still being developed. We discuss GI fistulas' clinical and radiological characteristics as well as its interventional management. This study intends to highlight the many GI organ-specific interventional management techniques for the treatment of postoperative GI leakage.